Teaching proficiency of pre-service secondary teachers in Eastern Samar State University-Salcedo Campus - Gaganao, Rovinson D.; Odon, Ma. Gracelda B. (Intelektual Pustaka Media Utama, 2024)
Competent teachers are attributed to student performance, school effectiveness, and the efficiency of an entire education system. Hence, this study compares the respondents' teaching proficiency across their profiles and correlates to their academic performance. The study utilized 30 pre-service secondary teachers of Eastern Samar State University Salcedo selected by complete enumeration, a descriptive comparative and correlational research design, and a questionnaire. Frequency, percentage, mean, and standard deviation were applied for descriptive analysis; t-test for comparison of respondents’ teaching proficiency; and Pearson’s correlation coefficient for the relationship between academic performance and teaching proficiency. The study revealed that respondents had a proficient teaching proficiency. Specifically, they were proficient in subject matter knowledge, lesson planning, classroom management, instructional strategies and motivation, communication skills, questioning skills, and professionalism. They have a very good academic performance in both professional education and major field of specialization. Furthermore, the study found no significant difference in the teaching proficiency across the respondents’ sex and age. However, a significant relationship was found between academic performance and teaching proficiency. Based on the findings, it is recommended that remedial classes on contents, pedagogies, and principles be provided especially for those respondents with low academic performance, to improve their teaching proficiency.